THE RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND INTRAOPERATIVE HYPOTENSION DURING CESAREAN SECTION USING SPINAL ANESTHESIA - Tri Budi Santoso; Widodo Widodo; Nurul Istiqomah; Heni Purwaningsih (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
The incidence of hypotension as a complication of spinal anesthesia in mothers who gave birth by cesarean section can occur due to various factors such as height, age, weight. The incidence rate in Indonesia in 2017 was 983 cases. In the preliminary study, there were 352 deliveries, of which 108 were delivered by cesarean section using spinal anesthesia techniques. Objective: to determine the relationship between maternal characteristics and the incidence of intraoperative hypotension for sectio caesarea using spinal anesthesia at Hospital "A". Research Methods: this study used cross-sectional. The research population of sectio caesarea patients with spinal technique was collected with a total sampling of 46 respondents. The research instrument used medical records. Analysis of the data used in the form of chi-square test at a significance of 5%. Results: The results of the bivariate test showed that there was no relationship between early adulthood (20-29 years) (OR= 0.38; (95% CI= 0.10 to 1.44; p= 0.259); multipara parity (OR= 0.44; (95% CI) = 0.11 to 1.67; p = 0.365) and obesity BMI (OR = 1.59; (95% CI = 0.48 to 5.35; p = 0.650) on the incidence of hypotension in caesarean section Conclusion: There is no relationship between early adulthood (20-29 years), parity and obesity BMI are risk factors for hypotension in cesarean section.